2009
DOI: 10.1210/en.2009-0526
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hypothalamically Mediated Acute-Phase Inflammatory Responses to Lipopolysaccharide in Diet-Induced Obese Rats

Abstract: Recent evidence suggests that inflammation may be a common underlying cause of many obesity-associated conditions. To test whether obesity changes the response to inflammation, we investigated its effects on the acute phase of the inflammatory response to an endogenous pathogen, lipopolysaccharide (LPS). Diet-induced obese male Wistar rats exhibited an increased and prolonged fever response to LPS (100 microg/kg) relative to lean rats. LPS-treated obese rats also showed a greater increase in circulating TNF-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
68
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 83 publications
13
68
3
Order By: Relevance
“…Weight reduction in children can normalize inflammatory markers, which gives us hope that metainflammation can be modified after it has begun (140). However, there remain many gaps in our understanding of how early life events (e.g., rapid post-natal growth) affect lifelong risk for metabolic disease and what interventions may be tenable in this negatively influence substrate metabolism, storage, and absorption in these tissues (93,(102)(103)(104). In adipose tissue, experimental endotoxin infusion in humans rapidly induces chemokine and T cell activation genes and therefore may potentiate leukocyte crosstalk and amplify initial inflammatory responses (105).…”
Section: Resultsmentioning
confidence: 99%
“…Weight reduction in children can normalize inflammatory markers, which gives us hope that metainflammation can be modified after it has begun (140). However, there remain many gaps in our understanding of how early life events (e.g., rapid post-natal growth) affect lifelong risk for metabolic disease and what interventions may be tenable in this negatively influence substrate metabolism, storage, and absorption in these tissues (93,(102)(103)(104). In adipose tissue, experimental endotoxin infusion in humans rapidly induces chemokine and T cell activation genes and therefore may potentiate leukocyte crosstalk and amplify initial inflammatory responses (105).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, contrary to imipramine, small doses of morphine is able to reduce struggling behavior [46] together with hyperthermia [47]. Lipopolisaccharide injection is also accompanied by hyperthermia and is able to enhance the floating behavior, too [38,48,49]. However, it is contradictory, that a more active animal (reflected by increased struggling after imipramine) has lower heart rate and temperature and its activity prior to the test was also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,34,35) In studies when BT was measured after high-fat dietary intervention, either an increase or no change in BT have both been observed. 16,[19][20][21]36,37) Our results show that HSD and HLD produced hypothermia, whereas HFD did not influence BT. These inconsistent results are likely to be brought from the different kinds and content of fatty acids in the diets that influence biosynthesis and secretion of adipokines or lipid mediators, and characteristics of the cell membrane.…”
Section: Discussionmentioning
confidence: 47%
“…Pohl et al show that high-fat-fed rats have prolonged fever after LPS injection, and concluded that this effect is mediated through an increase in circulating cytokines, especially leptin. 37) Another report demonstrated that leptin causes fever mediated through increased release of IL-1β and prostaglandins. 38) It has also been shown that FA modulates IL-1β-induced increases in monoamine turnover and PGE 2 level.…”
Section: Discussionmentioning
confidence: 99%